2004
DOI: 10.1111/j.1469-7610.2004.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of attention problems in children: longitudinal results from a study of twins, age 3 to 12

Abstract: OA and AP are highly heritable at all ages in both genders. The same set of genes appears to be expressed in boys and girls. The size of genetic and environmental contributions remains the same across the ages studied. Stability in OA and AP is accounted for by genetic influences. Children who do not display OA or AP at a given age are unlikely to develop these problems at a subsequent age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
131
5
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(161 citation statements)
references
References 73 publications
22
131
5
3
Order By: Relevance
“…The relevance of genetic influences across age groups was previously reported for attention problems and hyperactivity [45] and for aggressive behaviours [25,53].…”
Section: Discussionmentioning
confidence: 92%
“…The relevance of genetic influences across age groups was previously reported for attention problems and hyperactivity [45] and for aggressive behaviours [25,53].…”
Section: Discussionmentioning
confidence: 92%
“…If these contrast effects are not accounted for in the analysis, mother ratings will result in lower DZ concordance rates and successively in an overestimation of heritability. Rater contrast effects were described for the Rutter-A scale, the DBRS, parental interview data obtained by the CAPA (Table 1) and for the CBCL at age 3 only but not for children aged 7-12 years old [47,89,90].…”
Section: Rater Effectsmentioning
confidence: 99%
“…A third twin study assessed stability and change of CBCL-derived attention problems (AP) from age 3 to 12 years [90]. Correlation of age 3 measures with age 7,10, and 12 year old measures was between 35 and 40%; correlation of age 7 measures with age 10 and age 12 year measures was between 67 and 75%.…”
Section: Longitudinal Coursementioning
confidence: 99%
“…Here, twin studies have all shown that it is genetic factors that mainly account for continuity of ADHD symptoms over time. 28,[68][69][70] However, there is some additional genetic contribution specific to symptoms at the later time point in longitudinal studies. 28,68 This suggests that susceptibility genes for ADHD may also influence its continuity over time but that there may be additional genetic modifier loci that specifically influence the presence of symptoms at later ages.…”
Section: Persistence and Continuitymentioning
confidence: 99%